End to end secure e-voting using blockchain & quantum key distribution. (2023) - Gupta, Sweta; Gupta, Aparna; Pandya, Ishan Y.; Bhatt, Abhishek; Mehta, Komal
Abstract: A blockchain is a revolutionary computational data structure that enables an open, public, distributed ledger with a wide range of uses. Any new cryptographic application, on the other hand, should take into consideration expected technical improvement during the lifetime of any possibly deployed systems, many of which will be in use for decades. This document addresses the weaknesses of blockchain technology as a result of the development of quantum computers, as well as general recommendations for making blockchain more resistant to such technological breakthroughs. As a result, utilizing a special approach, this work shows many steps of the suggested electronic voting system. The method contains the idea of electronic voting using Quantum key distribution and blockchain security. Explicitly an extended version of the blockchain-based e-voting system to several networks applications. This work also describes the architecture, design, and design constraints of such a voting system in our society with implementation implications.